Poly-γ-glutamic acid coating polymeric nanoparticles enhance renal drug distribution and cellular uptake for diabetic nephropathy therapy. (2nd January 2023) - Wang, Qili; Han, Shunping; Zhu, Yongqin; Wang, Guowei; Chen, Danfei
Abstract: Poor drug distribution and inefficient renal cellular uptake are the major barriers diminishing the efficacy of nanoparticles in renal targeted therapy. We designed the rhein (RH)-loaded poly-γ-glutamic acid (PGA)-coated polycaprolactone-polyethyleneimine nanoparticles (RGPP) to enhance renal drug distribution and cellular uptake via PGA-mediated receptor-ligand interaction with γ-glutamyltranspeptidase (GGT) expressed highly in the kidney. PGA coating not only ensured the stability, sustained drug release, and biocompatibility of RGPP, but also promoted renal cellular uptake via binding with the GGT on the renal cells. Following intravenous administration, PGA coating protects RGPP from recognition by the reticuloendothelial system, resulting in prolonged blood circulation. RGPP enables targeted RH accumulation in the kidneys of streptozotocin-induced diabetic nephropathy (DN) mice, resulting in significant recovery of renal physiological function. The PGA coating strategy opens a new avenue for the management of renal diseases using nanomedicine.